2017
DOI: 10.1093/jjco/hyx001
|View full text |Cite
|
Sign up to set email alerts
|

First-line bevacizumab plus paclitaxel in Japanese patients with HER2-negative metastatic breast cancer: subgroup results from the randomized Phase III MERiDiAN trial

Abstract: Bevacizumab-paclitaxel efficacy in Japanese patients was consistent with the MERiDiAN ITT population. No new safety signals were seen and tolerability was consistent with previous experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
3
7
1
Order By: Relevance
“…Safety results in the Japanese subgroup population were consistent with the overall population, although there was a higher incidence of alopecia, peripheral sensory neuropathy, decreased neutrophil count, nasopharyngitis and decreased white blood cell count and a lower incidence of fatigue than in the overall population. Higher incidences of neutropenia and peripheral sensory neuropathy in Japanese and Asian patients have also been reported in other clinical trials (24, 26–29). Overall, atezolizumab was well tolerated with no treatment-related deaths, although more patients in the atezolizumab arm had neutrophil count decreases, nasopharyngitis, white blood cell count decreases, stomatitis, vomiting and pruritis than patients in the placebo arm.…”
Section: Discussionsupporting
confidence: 69%
“…Safety results in the Japanese subgroup population were consistent with the overall population, although there was a higher incidence of alopecia, peripheral sensory neuropathy, decreased neutrophil count, nasopharyngitis and decreased white blood cell count and a lower incidence of fatigue than in the overall population. Higher incidences of neutropenia and peripheral sensory neuropathy in Japanese and Asian patients have also been reported in other clinical trials (24, 26–29). Overall, atezolizumab was well tolerated with no treatment-related deaths, although more patients in the atezolizumab arm had neutrophil count decreases, nasopharyngitis, white blood cell count decreases, stomatitis, vomiting and pruritis than patients in the placebo arm.…”
Section: Discussionsupporting
confidence: 69%
“…The use of indirect comparisons within this network meta-analysis adds additional information beyond the multiple direct comparison meta-analysis that have compared Bev + Tax, Bev + Cap, Bev + Tax+-Cap with Tax, Cap and with other new chemotherapy. According to our results, it is certain that the addition of bevacizumab improved PFS and ORR compared with chemotherapy alone, which is consistent with previous studies [7,8,21]. Moreover, we found that more patients who received Bev + Tax had an objective response than did those who received Bev + Cap, and that Bev + Tax is superior to Bev + Cap in therapeutic strategies ranking, but there was no significant difference between Bev + Tax and Bev + Cap on PFS in HER2-negative breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, sixteen studies were identified involving 589 patients that fulfilled the inclusion criteria in Fig. 1 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Figure 2 demonstrates all available direct comparisons across outcomes in this network meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence in support of the predictive role of pVEGF-A emerged from the MERiDian trial or from the separately published analysis exclusively focused on the subgroup of Japanese patients from this same study. 5,6 We have previously addressed treatment outcomes in a larger cohort of HER2-negative MBC patients treated with bevacizumab and paclitaxel in first-line chemotherapy. 7 In light of the evidence emerged from recent literature and within our previously established research pipeline on the role of anthropometric and metabolic determinants of treatment efficacy in breast and ovarian cancer, we have now focused on a more restricted subgroup of patients from the original cohort with available data on body mass index (BMI) values at baseline assessment.…”
Section: Introductionmentioning
confidence: 99%